Arkaisk religion, komparation, norrøn og mesopotamisk - Lundager Jensen, Hans J. (Religionsvidenskabeligt Tidsskrift, 2022)
SUMMARY: The contribution departs from the conceptual dilemma between ‘primary religions’ and ‘archaic religions’ relative to the trifunctional paradigm of Dumézil. Jens Peter Schjødt has shown that in the Scandivian triad of deities in Uppsala, the paradigm can be seen as abstract relations, but not through the individual gods. The trifunctional paradigm is present as an implicit inspiration, realized in an independent and original constellation. Similarly it is attempted to demonstrate the existence of the trifunctional paradigm in Mesopotamian religion, where the functions are even actually represented by deities. RESUME: Bidraget tager udgangspunkt i det begrebslige dilemma imellem ‘primære religioner’ og ‘arkaiske religioner’ i forhold til Dumézils trefunktionelle skema. Jens Peter Schjødt har vist, at i den norrøne gudetriade i Uppsala foreligger skemaet som abstrakte relationer, men ikke gennem de enkelte gude-skikkelser. Trefunktionsskemaet er til stede som en bagvedliggende inspiration, der realiseres som en selvstændig og original konstellation. På tilsvarende vis forsøges forekomsten af det trefunktionelle skema påvist i mesopotamisk religion hvor funktionerne endda faktisk repræsenteres af gudeskikkelser.